NEUROMOTOR PROFILE AND LIFESTYLE OF YOUNG PEOPLE WITH DISABILITIES IN DIFFERENT CLASSES OF INTELLECTUAL EDUCATION. (Fiep Bulletin - online, 2011)
The relationship between society and people with intellectual disabilities (ID) has gone through different ways throughout history. Objective: To evaluate the lifestyle and health-related physical fitness in students with learning disabilities enrolled in different grades of education. Methods: The sample comprised 79 students of both genders aged between 11 and 16 years. This is a cross-sectional study, which evaluated the lifestyle by questionnaire and physical fitness through the criteria suggested by PROESP-BR. Results: The inclusion of students had higher levels of physical fitness as well as 60% of pupils with special education not eating five servings of fruits and vegetables per day while only 29.1% of students claim the same inclusion (p.0.07) . According to the data of physical activity there is a significant difference of p
Keywords: Lifestyle; Physical Fitness; School inclusion